The 1992-93 EMS crisis and the South: Lessons from the Franc Zone system and the 1994 CFA Franc devaluation - Rodrigue Dossou-Cadja (European Historical Economics Society (EHES), 2024)
The CFA franc devaluation on 11 January 1994 stands out as the most significant reform within the Franc Zone system since political independences of former African French colonies in 1960, yet a topic shrouded into profound taboo. So far, the economic literature has failed to draw any connection between this pivotal event in African macroeconomic history and its historical context: the 1992-3 European Monetary System (EMS) crisis. Using the narrative approach coupled with quantitative analysis (DCC-MGARH-X and SVARs) and powered by an unprecedented set of archival data from the Banque de France, the Bank of England, and the Bundesbank (the latter two from Eichengreen and Naef, 2022), as well as the International Monetary Fund (IMF), we document a brand-new route on understanding a certain integrated African-European common history. Evidence unveils the CFA franc devaluation as a fundamental role player in backing up credibility of the French franc amidst the 1992-3 EMS crisis. A 'new democratic Franc Zone's Transition Committee' at the Banque de France, appears as a key feature for the future of the Zone's management
Keywords: E42; E58; F31; F33; F42; F53; F54; F55; N14; N17; N24; N27; 330; CFA franc devaluation; Franc Zone; European Monetary System; Currency crisis; Political independences; Narrative approach